Reaktualisasi Kerukunan antar Umat Beragama dalam Kemajemukan Sosial - Mawardi Mawardi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2015)
Religious plurality is an inescapable phenomenon because every religion emerged from diverse situations and places. If the religious plurality is understood unwell and unwisely, it would potentially trigger problems among believers that impede Indonesian democracy system. To figure out resolution for religious conflict, it requires new appropriate approaches. On the other hand, it is also necessary to have religious tolerance to avoid racial conflict among believers that are characterised with highness, genteelness, politeness, and respectfulness to all form of worships. This article re-discusses the actualization of religious harmony in plural community.